2018
DOI: 10.1128/mspheredirect.00131-18
|View full text |Cite
|
Sign up to set email alerts
|

The Heteroaryldihydropyrimidine Bay 38-7690 Induces Hepatitis B Virus Core Protein Aggregates Associated with Promyelocytic Leukemia Nuclear Bodies in Infected Cells

Abstract: Despite the availability of effective vaccines and treatments, HBV remains a significant global health concern, with more than 240 million individuals chronically infected. Current treatments are highly effective at controlling viral replication and disease progression but rarely cure infections. Therefore, much emphasis is being placed on finding therapeutics with new drug targets, such as viral gene expression, covalently closed circular DNA formation and stability, capsid formation, and host immune modulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 71 publications
8
33
0
Order By: Relevance
“…3C), while treatment with GLS4 caused capsids to form large aggregates spread in the cell (Fig. 3D), as previously reported for this type of HAP derivatives (23)(24)(25)(26).…”
Section: Figsupporting
confidence: 86%
“…3C), while treatment with GLS4 caused capsids to form large aggregates spread in the cell (Fig. 3D), as previously reported for this type of HAP derivatives (23)(24)(25)(26).…”
Section: Figsupporting
confidence: 86%
“…Nuclear HBc was suggested to regulate HBV transcription by interacting with cccDNA (17,22). Interestingly, we found, like a very recently published study (50), that CAM treatment induces the relocalization of nuclear HBc to subnuclear sites staining positive for the 20S proteasomal subunit and PML bodies, which are the sites of protein posttranslational modification, activation, sequestration, or degradation (45). Here, we found that BAY41 treatment led to the formation of large HBc aggregates, whereas AT130 treatment had no effect or only a slight effect on nuclear HBc distribution.…”
Section: Discussionsupporting
confidence: 88%
“…Core protein (Cp)-deficient pHBV was constructed by introducing a premature stop codon to Cp in pHBV by site-directed mutagenesis with primers 5′-GGAGATCTCAGACGGAAGGAAAGAAGTC-3′ and 5′-GACTTCTTTCCTTCCGTCTGAGATCTCC-3′. The HBV core expressing plasmid (pC183) was described previously [35]. The eYFP-MOV10 plasmid was described previously [23].…”
Section: Methodsmentioning
confidence: 99%
“…Sequences of forward and reverse primers used for HBV DNA quantification were 5’-CCTGGTTATCGCTGGATGTGT-3’ (nt 364 to 384) and 5’-GGACAAACGGGCAACATACCTT-3’ (nt 479 to 458), respectively. These primers targeted conserved regions in the HBV S gene [35,39]. HBV DNA was quantified using ABsolute qPCR SYBR green mix (Thermo Scientific, Waltham, MA, USA) or Applied Biosystems™ PowerUp™ SYBR™ Green Master Mix, in a PikoReal real-time PCR system.…”
Section: Methodsmentioning
confidence: 99%